INVESTMENT COLLECTION STRATEGY OF START-UP SOCIAL CROWDFUNDING - Khozin Zaki; Erlin Estiana Yuanti (STIESNU Bengkulu, 2019)
Abstract One of the potential agro-industries is the fisheries sector. Many of the people of Indonesia are starting to realize that fishing businesses or businesses provide significant benefits. However, the orientation that fisheries is a profitable sector has not been able to convince the parties with excess capital to invest in this sector. This can be caused by the company not using the right strategy in gathering investment. One of the investment management services in the agro-industry sector, especially fisheries in Yogyakarta, which has a breakthrough in the collection strategy is a start-up named Iwak.me. The method used in this research is field study and literature study, field study is carried out through a direct observation process looking at the process of investment collection management and related activities plus interviewing the owners and employees of Iwak.me. The literature study was conducted by examining several sources of reading such as books, articles, and related news and company documentation. From the observations the author gets a description of the investment collection strategy that starts from the stage of company introduction, program campaigns, information services, and registration. Keywords: Investments, Investment Collection, Strategy, Social Crowdfunding Abstrak Salah satu sektor agroindrusti yang potensial adalah sektor perikanan. Banyak diantara masyarakat Indonesia yang mulai menyadari bahwa bisnis atau usaha perikanan memberikan keuntungan yang tidak sedikit. Akan tetapi untuk orientasi bahwa perikanan merupakan sektor yang menguntungkan belum dapat meyakinkan para pihak yang berkelebihan modal untuk berinvestasi pada sektor ini. Hal tersebut bisa disebabkan oleh perusahaan belum menggunakan strategi yang tepat dalam mengumpulkan investasi. Salah satu jasa pengelola investasi sektor agroindustri terutama perikanan yang ada di Yogyakarta yang memiliki terobosan dalam strategi pengumpulan adalah sebuah start-up bernama Iwak.me. Metode yang di gunakan dalam penelitian ini adalah studi lapangan dan studi pustaka, studi lapangan dilakukan melalui proses observasi langsung melihat proses manajemen pengumpulan investasi dan aktifitas yang terkait ditambah mewawancarai pemilik dan karyawan Iwak.me. Adapun studi pustaka dilakukan dengan menelaah beberapa sumber bacaan seperti buku, artikel, dan berita terkait serta dokumentasi perusahaan. Dari hasil observasi penulis mendapatkan deskripsi mengenai strategi pengumpulan investasi yang dimulai dari tahapan pengenalan perusahaan, kampanye program, pelayanan informasi, dan registrasi. Kata kunci: Investasi, Pengumpulan Investasi, Strategi, Crowdfunding Sosial